FORMULASI DAN EVALUASI AKTIVITAS ANTIOKSIDAN SABUN CAIR BERBAHAN DASAR EKSTRAK DAUN KEMANGI DAN MADU - Dewi, Bheta Sari; Utami, Sheila Meitania; Werawati, Ayu; Bachtiar, Wahyu; Dewantoro, Agung (PHRASE (Pharmaceutical Science) Journal, 2024)
Basil leaves  (Ocimum sanctum L.) and honey contain flavonoids and polyphenol compounds such as methyl eugenol, which are known to have antioxidant activity. Liquid soap is a form of pharmaceutical product that is often used to cleanse the body and provide additional protection to the skin. Objective: The aim of this study was to obtain the best physical formulation of a liquid soap combination of basil leaf extract and honey and its antioxidant activity. Method: Liquid soap preparations were made by adding basil leaf extract with various concentrations of 2g (FI), 4g (FII) and 8g (FIII) and honey, namely 5g (FI), 5g (FII) and 5g (FIII). Evaluation of liquid soap preparations included organoleptic, pH, and homogenity, as well as antioxidant activity test using the DPPH (1,1-diphenyl-2-picrylhydrazyl) method with a wavelength of 516 nm. Results: The results showed that Formula III (FIII) had the best results, namely organoleptic milk chocolate color, pH preparation (9.71-9.89), homogeneous preparation, stable preparation in storage for 12 days and showed the best IC50 value of 118.39 ppm. Conclusion: In conclusion, the combination of basil leaf extract and honey can be formulated as a liquid soap preparation with a concentration of 8g basil leaf extract and 5g honey in formula III (FIII) showing the effectiveness as the best formulation.